PELATIHAN JURNALISTIK DAN PUBLIC SPEAKING PETANI DALAM MENANGKAL ISU NEGATIF KELAPA SAWIT - Mulono Apriyanto; Akbar Alfa; Yoyon Riono; Khairul Ihwan; Marlina Marlina; Jamri Jamri (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
This service aims to improve the ability of farmers and members of the APKASINDO DPW in Riau and Banten to understand and practice journalistic problems, especially writing news articles. The method used in this service is in the form of lectures, discussions, questions and answers, simulation of news article writing, and evaluation. The target of this service is training participants consisting of DPW APKASINDO members and farmers. The results of this service activity show that they get good scores in the simulation of article / news manuscripts. 90% have met the completeness criteria and passed 10% are still in the sufficient domain and need more practice in writing article scripts.